SORPTIVITY AND CHLORIDE PENETRABILITY EVALUATION OF CONCRETE INCORPORATING FLY ASH AND SILICA FUME - Wahyuniarsih Sutrisno; Gabriel Ghewa; Priyo Suprobo (Journal of Civil Engineering, 2019)
Diffusion is one of the the main mechanisms of fluid ingress into the concrete. However, in partially saturatedconcrete, the fluid will mainly be absorbed by the capillary suction mechanism, which associates with the sorptivity propertiesof the concrete. This paper presents the results of an experimental program to investigate the influence of Portland cementsubstitution with Silica Fume (SF) and Type F Fly Ash (FA) on the rate of absorption, which also known as sorptivity, andchloride penetration of concrete. The sorptivity of the concrete was evaluated according to ASTM 1585, while the chloridepenetration was evaluated according to ASTM C 1202. By substituting part of cement with FA and SF, it was found that thesorptivity of concrete is reduced. Furthermore, all type of concrete with supplementary material, including CFA, CSF andCSM, is confirmed to enhance the ability of concrete to resist chloride penetration compared yo normal concrete (NC).